Land conservation on banana cultivation based on erosion risks level at Jenawi District-Karanganyar, Indonesia. (November 2018) - Herawati, A; Mujiyo; Widijanto, H; Isnaini; Romdhati, F
Abstract: Global climate change has impacts on the increase of annual rainfall. The raising of air temperature will lead to more water evaporation into the air so the potential for heavy rainfall will also increase, as well as the potential for soil damage. The aims of this research were (1) to determine the soil risk level on the existing condition and banana cultivation; and (2) to make proper land conservation directives on banana crops. This research is an explorative descriptive with survey approach at 28 land map units supported by soil analysis. The results showed that the erosion - risk levels were from low to very high, with erosion prediction of 0.24-1600.21 ton/ha/year and 9.88-2577.80 ton/ha/year on existing condition and banana cultivation. Contour bunds and bench terraces combined with permanent grass strips and annual crops planting are the alternative tools for land conservation methods at the surrounding areas.